2014
DOI: 10.5271/sjweh.3440
|View full text |Cite
|
Sign up to set email alerts
|

Assessing work ability – a cross-sectional study of interrater agreement between disability claimants, treating physicians, and medical experts

Abstract: This cross-sectional study quantifies disagreement in assessment of work ability of disability claimants referred to a multidisciplinary assessment center. The high level of disagreement calls for a careful evaluation of the disability assessment process in an effort to reduce the disagreement between expert teams, treating physicians, and claimants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Of 4562 potentially relevant citations identified, 101 reports proved potentially eligible after we had screened titles and abstracts. On full text screening, 23 studies, 9 11 22 23 24 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 including four non-English studies, 9 39 40 41 proved eligible for analysis (fig 1 ). All studies were published from 1992 onwards and enrolled disability claimants from 12 countries in Europe, North America, Australia, the Middle East, and northeast Asia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 4562 potentially relevant citations identified, 101 reports proved potentially eligible after we had screened titles and abstracts. On full text screening, 23 studies, 9 11 22 23 24 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 including four non-English studies, 9 39 40 41 proved eligible for analysis (fig 1 ). All studies were published from 1992 onwards and enrolled disability claimants from 12 countries in Europe, North America, Australia, the Middle East, and northeast Asia.…”
Section: Resultsmentioning
confidence: 99%
“… 9 11 22 23 24 32 34 37 39 43 44 45 46 Three studies including 3729 patients (with 3562 patients from a single centre 33 ) and eight raters (information was lacking from one study 33 ) explored agreement between medical experts and claimant’s treating physicians 33 or independent rehabilitation or occupational health teams with a mandate to care. 38 42 The median number of patients per study was 13.5 (range 1-3562), and the median number of raters per study was 12 (2-103, excluding one study that did not report the number of raters 33 ). All but three studies 24 3 42 used a fully crossed design (that is, all raters evaluated all patients), with a median of 11 patients (range 1-180) per rater and a median of 11.5 raters (2-103) per patient.…”
Section: Resultsmentioning
confidence: 99%
“…Work ability impairment has often been described as resulting from symptoms (Dell-Kuster et al 2014;Huijs et al 2012;Stansfeld et al 1995;Szubert and Sobala 2002). However, it has been found that the symptom itself does not predict work ability (Gatchel et al 1994).…”
Section: Toward a Concept Of Work Capacity Impairmentmentioning
confidence: 98%
“…A key criticism of disability evaluations is the failure of medical experts’ to clearly relate how claimants’ impaired health affects their ability to engage in competitive employment [ 14 – 18 ]. Rather, experts refer to their implicit professional expertise [ 11 , 12 , 19 , 20 ]. This gap is prevalent in work capacity evaluations independent of the underlying health condition, and may be a fundamental source for variation between expert judgments and contribute to low reliability of work capacity evaluations.…”
Section: Introductionmentioning
confidence: 99%